P20 Functional capacity is significantly impaired in primary biliary cirrhosis and related to orthostatic symptoms. (16th November 2010) - Patanwala, I; Newton, J; Patanwala, I; Elliot, C; Frith, J; Ghazala, C; Pariman, J; Jones, D
Abstract : Introduction: Primary biliary cirrhosis (PBC) is associated with a significant and diverse symptom burden independent of conventional markers of disease severity. It is unclear how this symptom load impacts upon function in day to day living and, if functional impairment is present, which symptom(s) are predominantly responsible. Aim: We assessed patient-reported functional ability and its inter-relationship with symptoms in PBC. Method: 81% (75/93) of the PBC symptom study cohort, originally derived in 2005, consisting of all PBC patients resident within the geographical area defined by zip codes NE1-NE25 (Newcastle-upon-Tyne and surrounding suburbs) completed a further set of postal-return symptom assessment tools in 2009. This included the disease specific symptom assessment tool the PBC-40, a marker of autonomic symptom burden, the Orthostatic Grading Scale (OGS), and the patient reported outcome measure health assessment questionnaires (PROMIS HAQ), that assesses functional ability (which was also completed by a liver disease control group (primary sclerosing cholangitis n=31 (PSC) and matched controls (n=55)). Results: Over 4 yrs of follow-up, total symptom burden, assessed using the cumulative PBC-40 domain scores, increased significantly (p=0.03). The predominant factor was a significant rise in Cognitive domain scores indicating worsening cognitive symptoms (p<0.0001). Functional impairment (PROMIS HAQ) was substantial in the PBC patients and exceeded that seen in the PSC controls. When the individual functional domains of the PROMIS HAQ were considered, we found that the PBC group had significant impairment in arising, eating, walking, reach and grip activity but not in dressing or hygiene. Functional impairment correlated positively with greater PBC-40 Fatigue, Cognitive and Social & Emotional domain scores and higher autonomic symptom burden determined by OGS score. Change in the PBC-40 Cognitive and Social & Emotional domain scores between 2005 and 2009 strongly predicted functional ability in 2009 Multivariate analysis confirmed that total PROMIS HAQ scores were predicted independently by PBC-40 Social & Emotional domain scores (p=0.02; β=0.3) and orthostatic symptoms (p=0.04; β=0.3). Conclusion: PBC is associated with a substantial impairment of functional capacity to a greater degree than has previously been appreciated. The distribution of symptoms of PBC evolves over time, with cognitive symptoms making an ever-greater contribution to the overall burden. The major determinant responsible for both functional impairment and the specific symptoms contributing to it appears to be autonomic dysfunction which is potentially modifiable by treatment.